A Context-aware Failure Detector for VANETs - Sá, Margarete; Gorender, Sérgio (Anais do Workshop Latinoamericano de Dependabilidade e Segurança em Sistemas Veiculares (SSV), 2025)
Vehicular Ad Hoc Networks (VANETs) are complex and dynamic networks that provide communication between vehicles. Due to its dynamism, it is difficult to adequately manage the resources and services of vehicular networks and to execute ITS (Intelligent Transportation Systems) applications reliably. In particular, applications developed to provide safe driving have strong requirements for vehicular communication, and this communication is provided without guarantees. In this paper, we present a context-aware failure detector service. This service uses Context information and Quality of Context metrics to improve the quality of detections. The concept of context has been developed for pervasive systems. It is used in VANETs to represent the status of a vehicle and its environment, including other vehicles and their communication. The failure detector service has been implemented in a simulation environment based on the Veins framework. The results demonstrate the effectiveness of the failure detector in using context and context quality metrics.